Внутриорганная лимфатическая система толстой кишки кролика - Чернышенко, Л.В. (Вестник зоологии, 1971)
On 86 macro-microscopic preparations оГ the rabbit different portions of large intestine Willi lymphatic vessles, injected with 1% solution of silver nitrate it was established that interglandular lymphatic capillaries (sinuses), which are located in the mucosa folds and run into small-looped subglandular net existing in the mucosa, are the roots of the lymphatic system of the rabbit large intestine. The small-looped subglandular net is located in the loops of large-looped net of the submucous layer as in frames. The absence in rabbits of supraglandular net which is present in men can be explained by difference in food composition. New data are obtained on endothelium of lymphatic capillaries in the mucous-submucous layer of large intestine. Argyrophility of endothelium cells in the mucous-submucous layer in large intestine is lower than that in small one. This is explained by the difference in functions of these organs.